Knowledge, attitude, and practice of pregnant women in preventing HIV transmission from mother to child - Helwiah Umniyati; Sri Puji Utami Atmoko; Mondastri Korib Sudaryo (Jurnal Kesehatan Ibu dan Anak, 2020)
HIV AIDS is a very important global health issue, and the trend of housewives getting HIV AIDS significantly increases. The objective of this study to assess knowledge, attitude, and practice related to mother-to-child HIV transmission and its prevention in antenatal clinic (ANC) attendees at the public health center. The type of studdy was a cross-sectional survey was conducted amongst 101 antenatal attendees in Senen Public Health Centre (Puskesmas) in Central Jakarta. The result was most respondents (83.2%) knew HIV caused AIDS. Knowledge of HIV prevention was quite good. Based on pregnant women's perception, only 25.7% had HIV test and 18% syphilis test in last pregnancy. In chi-square analysis, we found a significant relationship in variables knowledge of PMTCT, attended group discussion, and syphilis test related to attitude (p <0.05). The results of cox survival analysis, which was the lower the PMTCT knowledge, the worse the attitude (PR = 1.84 with 95% CI 1-072 - 3.150). Among the pregnant mothers, we found that the awareness and knowledge about HIV/AIDS were superficial.